Not to Carry Weapons Concealed; Where; nor Sell to Minors, etc., Ch. 43, An Ordinance in Relation to Dangerous and Deadly Weapons, § 3, in The Revised Ordinances of the City of Pattonsburg, Missouri (1902). - (:unkn) unknown (General Publisher, 1902)
Any person, who shall, within the corporate limits of said city, be found upon any street or alley, or upon premises not his own, without license from the owners or occupants thereof, having upon or about his person any kind of toy pistol which may be used for the purpose of discharging any missile by force of gun powder, or explosive caps, or exploding percussion caps or powder, shall, upon conviction, be fined in any sum not less than one nor more than one hundred dollars.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES